For a brighter tomorrow-a theoretical and empirical analysis of athletes' international migration - Klöcker, J. A.; Daumann, F. (Journal of Sports Economics, 2025)
The migration of professional athletes increased in volume and composition in the recent decades. We use a rational choice model to explain migration in certain sports and test it by applying the Poisson pseudo maximum likelihood estimator and the negative binomial pseudo maximum likelihood estimator. We can show that diaspora significantly impel the migration of athletes, while the GDP per capita is a significant pulling factor for athletics, but not for tennis and figure skaters. Considering the differences between nation's success in international competition, we find evidence for positive selection for athletes. With this study, we notably contribute to migration economics in the field of sport by analyzing migration in the sports of athletics, tennis, and figure skating for the first time.